2011
DOI: 10.5455/vetworld.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Antimicrobial activity and Minimum Inhibitory Concentration of Essential Oils of Spices

Abstract: Antibacterial activity and minimum inhibitory concentration (MIC) of essential oils of garlic, clove and cinnamon were estimated by using various bacterial pathogens. Among the bacterial pathogens tested against essential oil of garlic, Staphylococcus aureus was found to be highly sensitive followed by E.coli. L.monocytogenes and S.pyogenes were found to be less sensitive. The essential oil of clove was found to be most active against S.aureus followed by E. coli. B.cereus and C. jejuni. The essential oil of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
6
16
1
1
Order By: Relevance
“…The efficacy of essential oil of cinnamon in inhibiting human bacterial pathogens was determined by many researchers with varying reports depending upon the microorganism tested. The results of the present study were in agreement with previous reports demonstrating the inhibition of E. coli by cinnamon (2,3).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…The efficacy of essential oil of cinnamon in inhibiting human bacterial pathogens was determined by many researchers with varying reports depending upon the microorganism tested. The results of the present study were in agreement with previous reports demonstrating the inhibition of E. coli by cinnamon (2,3).…”
Section: Discussionsupporting
confidence: 96%
“…The results of this study indicated that the bacterial pathogen tested against the cinnamon extracts was highly sensitive to its action and was comparable to earlier reports (2). Use of cinnamon as alternative in the control of urinary tract infection may help to circumvent dysbiosis and microbial drug resistance induced by the repeated use of antibiotics.…”
Section: Discussionsupporting
confidence: 89%
“…In our study a poly herbal mouth wash showed a comparable result when tested against VGS with known antibiotic viz., ampicillin. In a study pudina extract at 50% concentration showed a comparable zone of inhibition to that of our [13] reported that clove showed an inhibitory zone of 18 mm against S.pyogenes which exactly corroborates with our result. To conclude our mouth wash had an excellent antibacterial activity against both the tested oral bacteria.…”
Section: Mic and Mbcsupporting
confidence: 92%
“…Antibacterial activity of essential oil of cinnamon was maximum against Staphylococcus aureus [105] followed by E. coli and Campylobacter jejuni [106].…”
Section: Cinnamon: Antimicrobial Actionmentioning
confidence: 99%